Transformation of the educational paradigm in the context of the formation of academic leadership and the development of transprofessionalism - K. V. Vodenko (Ekonomika Nauki)
The study substantiates the need to change educational paradigms in accordance with the new challenges of the time and the emergence of the phenomenon of academic leadership and the advent of the era of transprofessionals. The purpose of this work is related to the study of the phenomena of academic leadership and transprofessionalism, their role in the development of the modern educational paradigm. The article analyzes mainly the university sector, in which the development of academic leadership and transprofessionalism is taking place. The results obtained allow us to identify the main directions of development of the existing education system and the role of academic leadership and transprofessionalism in it. The scientific novelty of the study lies in the totality of the results obtained, revealing the features of academic leadership and transprofessionalism, their influence on the change of educational paradigms. It is concluded that academic leadership can be achieved subject to both the introduction of innovative technologies into the educational process and the implementation of a set of measures aimed at preserving the fundamental knowledge that a graduate must master. Therefore, it is necessary to consider academic leadership in the context of the strategic perspective of maintaining Russia’s status as the largest scientific power in the modern world. The phenomenon of transprofessionalism acts as an adequate response from the point of view of leading educational institutions to the challenges of technological change characteristic of the modern era